Correlation between Knowledge and Family Support with Active Cadre’s Role - Ida Bagus Made Dwi Indrawan; Chatarina Umbul Wahjuni (Jurnal Berkala Epidemiologi, 2014)
One factor that can help 100% achievement of  Universal Child Immunization (UCI) village status at Public health center (PHC) is depend on cadre’s role in promoting the importance of immunization to baby mothers and to motivate baby mothers to follow immunization program. The research objective was to analysis factors that related with active cadres roles in UCI village status achievement. This was a cross sectional study with sample size used in this research was 63 cadres of Integrated health care post (Posyandu) which is selected by stratified random sampling from UCI village and non UCI village. Result of this research showed there were no significant correlation between age ( p = 0,523 ), level of education ( p = 0,459 ), years of being cadre ( p =0,818 ), work status ( p = 0,766 ), attitude ( p = 1,000 ), and Posyandu’s access ( p = 0,713 ) with active cadres role. However, chi-square test showed there were correlation between knowledge ( p =0,000) and family support (p = 0,001) with active role cadres. There was no difference of cadre’s role in UCI village and non UCI village ( p = 1,000 ). It can be concluded that there were a significant correlation between knowledge and family support with cadre’s role in UCI village achievement. The suggestion for department of health Surabaya and PHC is to do refreshing cadres by training regularly to increase cadre’s knowledge about immunization.